2010
DOI: 10.1103/physrevlett.105.207201
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ferromagnetism of Cu-Doped ZnO Films Probed by Soft X-Ray Magnetic Circular Dichroism

Abstract: We report direct evidence of room-temperature ferromagnetic ordering in O-deficient ZnO:Cu films by using soft x-ray magnetic circular dichroism and x-ray absorption. Our measurements have revealed unambiguously two distinct features of Cu atoms associated with (i) magnetically ordered Cu ions present only in the oxygen-deficient samples and (ii) magnetically disordered regular Cu2+ ions present in all the samples. We find that a sufficient amount of both oxygen vacancies (V(O)) and Cu impurities is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
150
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 25 publications
11
150
0
Order By: Relevance
“…Despite these developments, magnetic-impurity-based DMS oxides are the subject of intense debate as a result of the many inconsistent results related to secondary phase formation, unknown impurities or substitutionality, solubility, clustering and/or segregation of the magnetic impurities in the host oxide matrix [16][17][18]. More recently, there have been reports of FM in ZnO and other oxides (attributed to anionic vacancies) by doping with non-magnetic ions, but besides evidence from superconducting quantum interference device (SQUID) data [13][14][15], a necessary but not sufficient criterion [17,18], there has been no reliable element-specific evidence for FM in these cases, with the exception of recent publications [19,20]. To establish true FM in the DMS oxides and to differentiate from impurity artefacts, various magnetic measurements-ranging from extremely sensitive SQUID and optical magnetic circular dichroism (OMCD) measurements, which directly probe the spin-polarized bands, to element-specific soft X-ray magnetic circular dichroism (SXMCD) measurements-are required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these developments, magnetic-impurity-based DMS oxides are the subject of intense debate as a result of the many inconsistent results related to secondary phase formation, unknown impurities or substitutionality, solubility, clustering and/or segregation of the magnetic impurities in the host oxide matrix [16][17][18]. More recently, there have been reports of FM in ZnO and other oxides (attributed to anionic vacancies) by doping with non-magnetic ions, but besides evidence from superconducting quantum interference device (SQUID) data [13][14][15], a necessary but not sufficient criterion [17,18], there has been no reliable element-specific evidence for FM in these cases, with the exception of recent publications [19,20]. To establish true FM in the DMS oxides and to differentiate from impurity artefacts, various magnetic measurements-ranging from extremely sensitive SQUID and optical magnetic circular dichroism (OMCD) measurements, which directly probe the spin-polarized bands, to element-specific soft X-ray magnetic circular dichroism (SXMCD) measurements-are required.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that it is the unambiguous fingerprint characteristics of X-ray absorption spectroscopy and XMCD as its magnetic counterpart obtained at both the O K-edge and the Cu L edges, which has led to this conclusion [176].…”
Section: Magnetic Semiconductorsmentioning
confidence: 70%
“…In this context, various non-magnetic dopants such as Cu, Al, K have been extensively studied for possible RT ferromagnetism in ZnO. [4][5][6][7][8][9][10][11] Ma et al observed RT FM in Al doped ZnO after vacuum annealing and ascribed it to the charge transfer between Al and ZnO, which can cause the electronic structure alternation of Zn and Al. 5 Ferromagnetism was reported in Cu doped ZnO by Tiwari et al and led to the conclusion that concentration of n-type carriers should not exceed a critical value after which the ferromagnetism completely vanishes.…”
Section: Introductionmentioning
confidence: 99%
“…10 Herng et al reported the existence of ferromagnetism in Cu doped ZnO thin films prepared by pulsed laser deposition (PLD) in oxygen deficient environment and identified that both oxygen vacancies (V O ) and Cu impurities are essential for the observed ferromagnetism. 4 Despite the numerous reports on the study of magnetism in non-magnetic dopants based ZnO, the origin of magnetism is highly controversial and it is still questionable that whether point defects are essential to explain magnetism in ZnO. Defects such as oxygen vacancies are deep donors that tend to form readily and have low formation enthalpies.…”
Section: Introductionmentioning
confidence: 99%